Comparative efficacy of decontamination methods for laparoscopic equipment: a systematic review and meta-analysis - Li, Jiajing; Gao, Shibin; Zhang, SuBo; Geng, Lei; Zhao, Yusheng; Zhang, Tao; Zhang, Lei; Li, Haiyang; Sun, Yi; Wan, Jinxin (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveTo compare the effectiveness of manual cleaning, alkaline multi-enzyme immersion with ultrasonic cleaning, and automatic reprocessing machines in decontaminating laparoscopes through a systematic review and meta-analysis of randomised controlled trials.MethodsA comprehensive literature search was conducted across PubMed, Embase, Cochrane Library, Web of Science, Sinomed, CNKI and Wanfang databases from inception to February 2025. Randomised controlled trials comparing different cleaning and disinfection methods for laparoscopes were included. The primary outcome was the qualified rate of decontamination, defined as meeting predetermined thresholds for each detection method (visual cleanliness, protein <6.4 μg/cm², ATP <200 RLU, negative occult blood). Heterogeneity was assessed using I² statistics, with subgroup analyses by detection method and intervention type. Risk of bias was evaluated using the Cochrane risk of bias tool.ResultsEleven randomised controlled trials involving 4,661 cases were included. Meta-analysis showed that alkaline multi-enzyme immersion with ultrasonic cleaning improved qualified decontamination rates compared with manual cleaning alone when assessed by visual inspection (risk ratio [RR] = 1.07, 95% CI: 1.02–1.13, P < 0.01) and occult blood test (RR = 1.12, 95% CI: 1.02–1.23, P < 0.05). The 7% improvement in first-pass cleaning qualification translates to potentially preventing contamination in approximately 70 additional instruments per 1,000 processed. Automatic reprocessing machines showed similar improvements (RR = 1.08, 95% CI: 1.01–1.16, P < 0.05). Low heterogeneity (I² < 25%) was observed across most outcomes.ConclusionThe evidence suggests that combined cleaning methods provide modest but clinically meaningful improvements over manual cleaning alone, though certainty is limited by methodological constraints and geographic concentration of studies. Healthcare facilities should consider implementing enhanced protocols while weighing resource availability, training requirements, and local infection prevention priorities.